Delivering obstetrical critical care in developing nations - Bajwa, Sukhwinder Kaur (Medknow Publications & Media Pvt Ltd, 2012)
Obstetrical critical care has not been able to achieve the same level of peaks in developing nations like India, as in the western countries. Numerous factors, including clinical and economical, have played a major role in widening the gap of quality care delivery in severely ill obstetric patients, between the two extreme worlds. Moreover, this wide gap can be, to a large extent, attributable to the lower literacy rates, paucity of research in obstetrical critical care, poverty, lack of awareness, and the sociocultural and behavioral factors prevalent in these developing nations. The most common indication for Intensive Care Unit (ICU) admission of such patients throughout the world is hemorrhage, both antepartum and postpartum. Hypertensive disorders, pre-eclampsia, and its related complications are also major contributory factors for such admissions. The pattern of the disease necessitating such admissions influences maternal mortality to a great extent. The present article reviews the most common indications of obstetrical admissions to the ICU, the challenges and obstacles in the treatment of severely ill obstetric patients, their possible outcome in the developing nations, room for improvement, and the need for a change in the system for better delivery of critical care obstetrical services.